2010
DOI: 10.1111/j.1524-4741.2010.00976.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Breast Carcinoma: Clinical Characteristics and Its Impact on Survival

Abstract: The higher incidence of breast cancer, the improvements in diagnosis and treatment, together with the growing life expectancy have brought about an increase in the number of patients at risk for bilateral breast carcinoma. The aim of this study is to describe the characteristics of patients suffering from bilateral breast carcinoma who underwent surgery at the Breast Pathology Service of the Buenos Aires British Hospital and to analyze impact on survival. Between January 1970 and May 2007, 4,085 cases of breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
53
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 32 publications
2
53
1
5
Order By: Relevance
“…As our study does not include unilateral patient data, the median age comparison cannot be made with the BBC, it is compatible with the literature data. In above studies where BBC and UBC case ages are compared, statistically significant difference in ages of both groups have not seen (Takahashi et al, 2005;Vuoto et al, 2010;Kheirelseid et al, 2011).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…As our study does not include unilateral patient data, the median age comparison cannot be made with the BBC, it is compatible with the literature data. In above studies where BBC and UBC case ages are compared, statistically significant difference in ages of both groups have not seen (Takahashi et al, 2005;Vuoto et al, 2010;Kheirelseid et al, 2011).…”
Section: Discussionmentioning
confidence: 90%
“…Although there was difference between groups, the possible cause of this lower ratio than proportional UBC historical data is the presence of unknown group emergence with a relatively high rate of 11.7% and 27.8%. In one of two different studies evaluating the familial history in the context of the BBC (Vuoto et al, 2010), there were no significant differences between UBC and the BBC. In another study (Kheirelseid et al, 2011) it is suggested that it is increased in synchronous group with odds ratio of 1.5, also data in our study is in favor of SC.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations